The social media challenge for democracy: propaganda and disinformation in a platform society - Bradshaw, S (2020)
What is the nature of private platform authority and its causal and consequential role in shaping contemporary political communication and the spread of disinformation and propaganda online? This thesis integrates three distinct studies that examine how platform authority – including the technical, social, economic, and institutional practices of private companies – shape contemporary political communication and the creation and dissemination of propaganda and disinformation. By illuminating some of the hidden affordances of digital platforms and their algorithms, I explore how people find, watch, and discuss news and politics in a mediated environment that is increasingly characterized by attention economics, surveillance capitalism, and black-box decision-making. My first study examines the politics of Google Search and explores when keyword metadata generated top placements for “junk news” and other conspiratorial, hyper-partisan, or disinformation websites. My second study looks at the politics of Twitter and examines how hashtags and automation were used by foreign state actors to demobilize, target, and harass civil society activists working on issues pertaining to women’s rights and empowerment. My third study looks at the politics of YouTube, and how the introduction of state-backed media labels affected how users consume, comment on, and criticize information from these sources. Each of these chapters show that social media platforms all have affordances that are open for political manipulation by actors with very few resources and technical skills. But more importantly, these studies also demonstrate the importance of private actors for contributing to strong institutions of political communication in private spaces: we depend on Google Search, Twitter, and YouTube to faithfully implement technologies and policies that support the civic functions they often deny they perform. I show how the privatization of democracy – through the institutional and technical decisions of platform companies – shape public life, not always for the better.